Differential agar medium (A7) for identification of Ureaplasma urealyticum (human T mycoplasmas) in primary cultures of clinical material. - Shepard, M C (1976)
A differential agar medium for the identification of Ureaplasma urealyticum in primary cultures of clinical specimens is described. The differential medium (no. A7) is specific for the identification of U. urealyticum and other members of the genus Ureaplasma. Large-colony, classical Mycoplasma and Acholeplasma species and Proteus L colonies are unreactive on this differential medium. The medium incorporates the biochemical principle of the direct spot test for urease in colonies of Ureaplasma and contains added urea and a sensitive indicator of ammonia, manganous sulfate. Ureaplasma colonies on this medium are identified as dark golden-brown or rich deep-brown colonies, in sharp contrast to the light background of the medium, when viewed by direct transmitted illumination under the low power of the microscope.